The Triple Helix Model of Innovation: An Analysis of Scientific Production - Gálvez, Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This paper analyzes the scientific production on the Triple Helix model, based on the interaction between university-industry-government, which highlights the relevance of the role of universities in the transition from an industrial society to another based on knowledge. Bibliometric indicators and factor analysis techniques were used. A total of 593 publications indexed in the central collection of Web of Science (WoS) were retrieved, from 1993 to 2022. The most productive authors, countries, institutions and journals, the manuscripts with the greatest impact and the thematic and conceptual structure in the scientific field analyzed.